2021
DOI: 10.3390/v13081615
|View full text |Cite
|
Sign up to set email alerts
|

What Binds Cationic Photosensitizers Better: Brownian Dynamics Reveals Key Interaction Sites on Spike Proteins of SARS-CoV, MERS-CoV, and SARS-CoV-2

Abstract: We compared the electrostatic properties of the spike proteins (S-proteins) of three coronaviruses, SARS-CoV, MERS-CoV, and SARS-CoV-2, and their interactions with photosensitizers (PSs), octacationic octakis(cholinyl)zinc phthalocyanine (Zn-PcChol8+) and monocationic methylene blue (MB). We found a major common PS binding site at the connection of the S-protein stalk and head. The molecules of Zn-PcChol8+ and MB also form electrostatic encounter complexes with large area of negative electrostatic potential at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…PSs used in this study were monocationic 3,7-bis-(Dimethylamino)-phenazathionium chloride C16H18ClN3S (methylene blue, Samaramedprom, Samara, Russia) and octacationic octakis(cholinyl)zinc phthalocyanine (Zn-PcChol 8+ , Organic Intermediates and Dyes Institute, Moscow, Russia). The stick models with equipotential electrostatic surfaces of MB, with a total charge of +1, and Zn-PcChol 8+ with a total charge of +8, are shown in Figure 1 , in accordance with our previous study [ 22 , 27 ].…”
Section: Methodssupporting
confidence: 90%
See 4 more Smart Citations
“…PSs used in this study were monocationic 3,7-bis-(Dimethylamino)-phenazathionium chloride C16H18ClN3S (methylene blue, Samaramedprom, Samara, Russia) and octacationic octakis(cholinyl)zinc phthalocyanine (Zn-PcChol 8+ , Organic Intermediates and Dyes Institute, Moscow, Russia). The stick models with equipotential electrostatic surfaces of MB, with a total charge of +1, and Zn-PcChol 8+ with a total charge of +8, are shown in Figure 1 , in accordance with our previous study [ 22 , 27 ].…”
Section: Methodssupporting
confidence: 90%
“…Recently, we showed that both dyes, monocationic MB and octacationic Zn-PcChol 8+ , possess an affinity for negatively charged regions of coronavirus spikes, the main region of which is located at the connection of the S-protein stalk and the head on the linker between the HR1 and HR2 domains, adjacent to HR2 [ 22 ]. Incubation of BCoV for 10 min using these dyes leads to a deterioration in the resolution of spikes ( Figure 2 ) during electron microscopy, negatively contrasting with uranyl acetate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations